2013
DOI: 10.1007/s13753-013-0020-z
|View full text |Cite
|
Sign up to set email alerts
|

Flood-induced vulnerabilities and problems encountered by women in northern Bangladesh

Abstract: This study examines flood-induced vulnerabilities among women in northern Bangladesh. Poor and disadvantaged women are more vulnerable to disasters than men due to the conditions that predispose them to severe disaster impacts. Women suffer from physical injuries and are often evicted from their dwellings due to floods. Difficulties in finding adequate shelter, food, safe water, and fuel for cooking, as well as problems in maintaining personal hygiene and sanitation, prevent women from performing their usual r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(97 citation statements)
references
References 10 publications
2
93
0
2
Order By: Relevance
“…Unfortunately, women are more likely to be single heads of households, leading to an overrepresentation of single mothers, female widows, and divorced and elderly women in natural disaster mortality statistics (Ollenburger and Tobin ). Furthermore, such women are still restricted by purdah, exacting additional obstacles to single‐head female households when procuring disaster relief (Azad and others ).…”
Section: Why Women Die At Higher Ratesmentioning
confidence: 99%
“…Unfortunately, women are more likely to be single heads of households, leading to an overrepresentation of single mothers, female widows, and divorced and elderly women in natural disaster mortality statistics (Ollenburger and Tobin ). Furthermore, such women are still restricted by purdah, exacting additional obstacles to single‐head female households when procuring disaster relief (Azad and others ).…”
Section: Why Women Die At Higher Ratesmentioning
confidence: 99%
“…However, from country to country or region to region, women’s health status is generally violated in disasters. Of the large number of studies conducted on the detrimental health effects of disasters, the majority has revealed that women are more affected by natural disasters than men,4 indicating that women have a higher vulnerability to the impact of natural disasters 5–7…”
Section: Introductionmentioning
confidence: 99%
“…Surveys in one vulnerable region, the Jamuna River floodplain, report that 49% of households found it necessary to relocate during the period 1962−2016 due to flooding, with the vast majority resettling within 5 km of their previous location (Ferdous et al., 2019). Durations of major flood events along the Brahmaputra–Janina River during 1988−2007 ranged from 16 to 67 days (Ali et al., 2019), so even those not permanently relocating experienced lengthy displacements, lost livelihoods, reduced food and clean water intake, and inadequate sanitation (Azad, Hossein & Nasreen, 2013; Dewan, 2015).…”
Section: Short‐term Fluctuations In the Demand For Shelter And Servicesmentioning
confidence: 99%
“…Half of those displaced went temporarily to exposed sites including elevated roads, railways, embankments, and dams; about one quarter went to schools and community centers; and the remainder likely went to private homes and rentals (Azad, Hossein & Nasreen, 2013, p. 195). This contrasts starkly with the U.S. experience of moving mostly to motels and rental buildings.…”
Section: Short‐term Fluctuations In the Demand For Shelter And Servicesmentioning
confidence: 99%